2005
DOI: 10.1177/0091270005278600
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Warfarin When Coadministered With Pentosan Polysulfate Sodium

Abstract: The effect of pentosan polysulfate sodium on warfarin pharmacokinetics and pharmacodynamics was investigated in healthy subjects. Warfarin was titrated to an international normalized ratio between 1.4 and 1.8. Subjects continued their titrated dose of warfarin and received pentosan polysulfate sodium 100 mg or placebo every 8 hours for 7 days. The Cmax of R- and S-warfarin was approximately 840 to 890 ng/mL and 680 to 730 ng/mL, respectively, and was similar in the absence and presence of pentosan polysulfate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…58 In addition, it was reported that coadministering PPS (300 mg/day orally for 7 days) did not affect warfarin pharmacokinetics or pharmacodynamics. 59 PEGylation may change physical and chemical properties of the proteins. From previous reports, covalent PEGylation occasionally altered biological activity, which may be of concern.…”
Section: Biomacromoleculesmentioning
confidence: 99%
“…58 In addition, it was reported that coadministering PPS (300 mg/day orally for 7 days) did not affect warfarin pharmacokinetics or pharmacodynamics. 59 PEGylation may change physical and chemical properties of the proteins. From previous reports, covalent PEGylation occasionally altered biological activity, which may be of concern.…”
Section: Biomacromoleculesmentioning
confidence: 99%
“…The dose response relationship of warfarin differs between healthy subjects and can vary to a much greater extent among sick patients [3]. It can be influenced by many factors such as pharmacokinetic factors (due to differences in absorption or metabolic clearance of warfarin induced by drug interaction or patient base situation such as gender), pharmacodynamic factors (due to differences in the hemostatic response to given concentrations of warfarin) and technical factors including inaccuracies in laboratory testing and reporting, poor patient compliance, and poor communication between patient and physician [4][5][6]. Drug can influence the pharmacokinetics of warfarin by reducing its absorption from the intestine or by altering its metabolic clearance [3].…”
Section: Introductionmentioning
confidence: 99%
“…The study enrolled 18 healthy adult volunteers in a fixed sequence and had a 1-way crossover design with 2 periods. The subjects received a single dose of 25 mg warfarin (5 × 5-mg Coumadin tablets) on day 1 of period 1 (days 1-7) and again on day 14 of period 2 (days [8][9][10][11][12][13][14][15][16][17][18][19][20]. The subjects also received epacadostat 300 mg twice daily during days [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Methodsmentioning
confidence: 99%
“…Warfarin is a well‐recognized narrow therapeutic index (NTI) drug with risks of bleeding complications (overdosing) and thrombosis (underdosing) often necessitating dedicated clinical pharmacology studies to evaluate drug–drug interactions (DDIs) for warfarin as the victim drug . To reduce the risk of causing bleeding in trial participants, warfarin DDI studies are typically conducted in healthy volunteers administered either single doses of warfarin or multiple doses titrated individually to achieve stable subtherapeutic anticoagulation levels ranging from 1.2‐ to 1.7‐fold of baseline as measured by the international normalization ratio (INR) of prothrombin time (PT) . In actual clinical practice, higher levels of INR are targeted for different indications, for example, an INR of 2.5 (range, 2–3) for patients with venous thromboembolism and atrial fibrillation or an INR of 3.0 (range, 2.5–3.5) for patients with certain mechanical heart valves .…”
mentioning
confidence: 99%
See 1 more Smart Citation